Газодинамическое сопротивление и скорость звука в канале с гофрированной стенкой - Шевченко, Сергей Андреевич; Конох, Владимир Иванович; Макотер, Александр Петрович (НТУ "ХПИ", 2016)
Представлены результаты экспериментального исследования газодинамических характеристик гибкого металлического трубопровода с гофрированной оболочкой (металлорукава). Определены потери давления и коэффициент распределенного сопротивления металлорукава, используемого в составе испытательного стенда, работающего на сжатом воздухе. Впервые разработана оригинальная методика для определения скорости звука в канале с гофрированной стенкой. Полученные результаты используются для математического моделирования работы пневмосистемы запуска ракетного двигателя с регулятором давления на стадии стендовых испытаний.

Results of experimental research gas-dynamic characteristics of the flexible metal tubing with the corrugated shell (corrugated metal hose) have been presented. Pressure losses and distributed resistance factor of the corrugated metal hose as part of the test stand, which works on compressed air, have been determined. It has been shown that the resistance factor of corrugated metal hose exceeds the smooth pipe factor by order of the value. It can be calculated by Prandtl equation, if height of corrugation is used as parameter of roughness. It has been determined that at the analysis of rocket engine pneumatic starting system operation on the test stand it is necessary to take into account Joule-Thomson effect and heat exchange in the pressure regulator. For the first time the original methodology of sound velocity determination in the channel with the corrugated wall has been developed. These results are used for mathematical modeling of the pneumatic starting system in the development test stage.
Gas-dynamic resistance and velocity of sound in the channel with the corrugated wall
Keywords: металлорукав; пневматический стенд; коэффициент расхода; эффект Джоуля-Томсона; corrugated metal hose; pneumatic stand; flow coefficient; Joule-Thomson effect